Association of serum uric acid level with angiographic severity of coronary artery disease: a study in a tertiary care hospital, Chittagong, Bangladesh - M. Ismail, Khondaker; Kumar Das, Prabir; Awal, Anisul; Das, Saurav; Latif, Sayem Bin; Bashiruddin, M. A. B. K.; Hasan, M. Mehadi; Easmin Eva, Tania; Hossan, M. Sawkat; Bhattacharyya, Partha (International Journal of Research in Medical Sciences, 2023)
Background: Coronary artery disease (CAD) is a major global health issue. Serum uric acid (SUA), a byproduct of purine metabolism, is linked to CAD development and progression. Elevated SUA levels are an independent risk factor for cardiovascular mortality and may indicate endothelial dysfunction. The aim of the study was to the observed associate serum uric acid level with the angiographic severity of CAD. Methods: This observational study was conducted at Chittagong medical college hospital in Bangladesh from October 2020 to September 2021. It included 130 patients and used unpaired t-tests to analyze the association between serum uric acid level and angiographic severity of CAD patients. Ethical clearance was obtained from the institutional review board of Chittagong medical college and hospital. Results: A study of 130 patients found a significant relationship between serum uric acid (SUA) levels and CAD (CAD), vessel involvement, and CAD severity (p=0.001). Patients with CAD had higher SUA levels (mean 5.26±1.32 mg/dL) compared to those without CAD (mean 4.22±1.03 mg/dL). A SUA level range of 3.94-6.58 mg/dL was associated with CAD presence. Gender also showed a highly significant association with SUA levels (p=0.001), while age, BMI, and smoking status did not show significant differences. Conclusions: A strong positive association has been found between serum uric acid level and the severity of CAD. The findings of this study approve the effectiveness of hyperuricemia as an emerging risk factor for CAD.